Surdos em ambientes virtuais de aprendizagem: primeiros contatos e primeiras impressões - Schuskel, Débora (2009)
One of the challenges of the use of technology (the Internet, for example) in areas of educational collaborative learning is the promotion of respect for the singularity of individuals recognition of differences as well as the continuing quest for social integration of all beings involved in this process. Issues like these need to be observed with more attention and become a priority in face-to-face and virtual educational environments. Based on the need to reflect on the singularities of the deaf in virtual environments, this study proposes an analysis of virtual learning environments, focusing on the first contacts and first impressions of deaf people with this "new" possibility of communication. This study involved a group of six deaf individuals who were invited to access one of the virtual learning environments from an on-line course developed by the Distance Education team of the Foundation of Administrative Development (Fundap). The proposal was to create the opportunity to discuss a distance education online course in which deaf individuals would be the main contributor in the dynamic of construction of meaning and, thereby, enlarge their natural conditions as individuals. The deaf subjects accessed the online Course Communication for Pregoeiro and, in contact with that environment, had the opportunity to express their first impressions about what was understood. During such access, the researcher recorded the subject s comments using video (all meetings with deaf subjects were filmed and then transcribed, since most of the communication between them used sign language LIBRAS). This contact allowed the emergence of the difficulties and facilities encountered by the deaf in using this learning environment. Moreover, based upon their opinion it is possible to recognize that new strategies are needed for deaf individuals to be able to more adequately use virtual learning environments